IMPLEMENTASI KEBIJAKAN E-GOVERNMENT DALAM PENYELENGGARAAN PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MAMUJU PROVINSI SULAWESI BARAT - Satiawati, Willia; Rumapea, Patar; Pombengi, jericho Danga (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACK: The Iimplementation policy of e-government in management public service is one of the government programs by making use of information and technology in management public services more effective and efficient. But in reality the service performed has not gone up, therefore, the research is intended to answer questions about How The Implementation policy of e-government in management of public service in the Department of Population and Civil Registration Regency of Mamuju, West Sulawesi province. In this study, researchers used a model of implementation of the George C. Edward III, where the implementation level visits from four aspects which have great impact in policy implementation. Communication is an aspect for the government to inform policy to the public as target group. Adequate resources both human resources and financial resources will be influence the success rate policy. Disposition is the attitude held by implementing policies such as ethics, and commitment to make this policy succeed. The bureaucratic structure is mechanism service operations and the structure of society together implementing agency policies. In this research using descriptive method qualitative research is conducted to 9 informant interviews, direct observations, and search any documents that relate to the policy, even in research aided by interview, a tape recorder, and stationery. The results of research in general explained that the implementation of e-government policies in public service in the Department of Population and Civil Registration Mamuju, West Sulawesi province has not gone up.Keywords: Policy Implementation, Management of Public Service